FACTORS AFFECTING USE BEHAVIOR TO USE TRANSPORTATION SERVICES APPLICATIONS USING UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) 2 MODEL - Santoso, Budi Setiawan; Siregar, Suzanna Lamria (Universitas Gunadarma, 2018)
This research is motivated to analyze the technology acceptance of the Transportation Services Applications in Jabodetabek using Unified Theory of Acceptance and Use of Technology (UTAUT) 2 model. The purpose of this research is to determine the factors based on UTAUT 2 model for the use behavior to use the Transportation Services Applications in Jabodetabek and to test the UTAUT 2 model whether the model is suitable for this research to assess which factors that affect the use behavior of those applications or not. Population in this research is the people who live in Jabodetabek and the sample size is 238. The methodology used in this research consists of literature review and data analysis. The result shows that only four variable factors that affect the use behavior to use the Transportation Service Applications namely Habit, Social Influence, Price Value and Behavioral Intention. The analysis result shows that UTAUT 2 model is suitable and fits the empirical data of the research, it means that the use behavior of Transportation Services Applications can be explained by UTAUT 2 model.